ANALISIS KEDISIPLINAN PADA PROSES PEMBELAJARAN SISWA KELAS IV SD NEGERI 5 BULUNGCANGKRING - Naufal Ainur Rahman; Ika Ari Pratiwi; Wawan Shokib Rondli (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
ABSTRACT This research aims to describe to describe the application of discipline as well as supporting and inhibiting factors for discipline in the learning process of class IV students at SD N 5 Bulungcangkring. This research is a qualitative descriptive research. The research subjects were students teachers and parents. The object of this research is discipline in the learning process. This research uses data collection techniques in the form of observation, interviews, and documentation. Data analysis uses Miles and Huberman interactive model analysis techniques (data reduction, data display, and drawing conclusions). Test validity using triangulation of techniques and sources. The results of the research show that class IV students have discipline which includes punctual arrival and departure times, students obligations, students prohitions, and the use of clothing/uniforms in participating in the learning process. During the learning process, students are less disciplined in obeying the rules, especially in relation to the obligation to do assignments. Factors that support students discipline in the participating in the learning process at school are teacher factors, rules and the applications of educational punishments/sanctions. The inhibiting factor for students disciplined in following the learning process at school is the influence of friends who are not disciplined. Keywords : Discipline, Learning, Class IV Students ABSTRAK Penelitian ini bertujuan untuk mendeskripsikan penerapan kedisiplinan serta faktor pendukung dan penghambat kedisiplinan pada proses pembelajaran siswa kelas IV SD N 5 Bulungcangkring. Penelitian ini merupakan penelitian deskriptif kualitatif, Subjek penelitian adalah siswa, guru, dan orang tua. Adapun objek penelitian ini adalah kedisiplinan pada proses pembelajaran. Penelitian ini menggunakan teknik pengumpulan data berupa observasi, wawancara, dan dokumentasi. Analisis data menggunakan teknik analisis model interaktif Miles dan Huberman (reduksi data, display data, dan penarikan kesimpulan). Uji keabsahan menggunakan triangulasi teknik dan sumber. Hasil penelitian menunjukkan bahwa siswa kelas IV memiliki kedisiplinan yang meliputi ketepatan waktu datang dan pulang, kewajiban siswa, larangan siswa, serta penggunaan berpakaian/berseragam dala mengikuti proses pembelajaran. Saat proses pembelajaran siswa kurang disiplin dalam ketaatan terhadap tata tertib terutama kaitannya dengan kewajiban mengerjakan tugas. Faktor pendukung kedisiplinan siswa dalam mengikuti proses pembelajaran di sekolah adalah faktor guru, tata tertib, serta penerapan hukuman/sanksi yang mendidik. Untuk faktor penghambat kedisiplinan siswa dalam mengikuti proses pembelajaran di sekolah adalah dari teman yang tidak disiplin. Kata Kunci : Kedisiplinan, Pembelajaran, Siswa Kelas IV.